The Arabic language and the challenges it faces - souigat, ismail (El Omda in Linguistics and Discourse Analysis, 2025)
The Arabic language in the Arab world faces many difficulties, some external and some internal, and this article tries to diagnose some of the difficulties faced by the Arabic language in Algeria, especially since the French colonialism and ending in the post-independence phase, proposing a number of measures that the research believes will contribute to keeping the Arabic language in line with the year of development and thus can face these difficulties and get out of this conflict and this impasse in which it is with the least losses because the battle against it is severe and the conflict it is fighting against what threatens Its entity is raging and if its people do not take the initiative to deal with it and remedy it, what may happen to it in some languages when it enters the clinical phase followed by death, God forbid.